An alternative to the classical specification of boundary conditions in finite element stress analysis - Brown, Christopher John (Department of Mechanical Engineering, 2024)
[Page 1 missing] A development of the displacement method of finite element analysis is presented which serves to effectively bypass conventional boundary condition specifications. Indeterminate equations pertaining to boundary degrees of freedom are replaced in the assembly matrix by an alternative form of equation ?ased on the strain/displacement relationship of finite elements; The computer progranuning of the proposed method is described, and a series of proving runs made on typical mesh configurations is discussed.